Pengembangan Instrumen Tes Keterampilan Teknik Dasar Bermain Bola Tangan: Norma Tes Keterampilan Teknik Dasar Bermain Bola Tangan - Perdana, Habain Sila; Widodo, Ahmad; Wahyudi, Heri (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
A series of tests of special technical skills in handball games, for handball players that match the characteristics in actual handball training and matches. The norms of passing and catching tests carried out with wall media for 30 seconds with the acquisition of values 15 times down the category Less Once, 16-25 times the category is less, 26-55 times the category is moderate / sufficient, 56-65 times the category is good, and 66 times and above the category is very good. Within a distance of 7 meters shooting to the goal obtained target target 0 then the category is very less, target target point 1 category is less, target target point 2 is moderate, target target point 3 is good, and target target point 4 is very good. While the speed of the shot time obtained time above 0.58 seconds is classified as a very poor category, time 0.52-0.57 seconds is classified as a poor category, time 0.38-0.51 seconds is classified as moderate, time 0.30-0.35 seconds is classified as a good category, and time under 0.29 seconds is classified as a very good category. In a distance of 9 meters shooting to the goal obtained target target 0 then the category is very less, target target point 1 category is less, target target point 2 is moderate, target target point 3 is good, and target target point 4 is very good. While the speed of the shot time obtained time above 0.61 seconds is classified as a very poor category, time 0.56-0.6 seconds is classified as a poor category, time 0.42-0.55 seconds is classified as moderate, time 0.37-0.41 seconds is classified as a good category, and time below 0.36 seconds is classified as a very good category. Based on the data that has been analyzed, it can be concluded as follows: 1. The series of passing and catching technique tests using wall media is carried out for 30 seconds.2. The series of shooting technique tests for bolatangan games consists of 3 types of tests that cannot be separated from one another and are a single unit. 3. The types of shooting technique skill tests selected to be a series of technical tests in bolatangan games: a) Fly Shoot tests carried out at a distance of 7 and 9 meters in the middle. b) Standing Shoot tests carried out at a distance of 7 and 9 meters right in the middle position straight with the goalkeeper. c) Side Shoot tests carried out with a distance of 7 and 9 meters with a position in the middle straight with the goalkeeper. Keywords: passing and catching test, goal shooting test, test norms.